(untitled) (Dharma: Jurnal Pengabdian Masyarakat, 2025)
Seleraku MSME in Lengkong Village, Banjarnegara Regency, faces challenges in product packaging due to its reliance on manual methods that result in inconsistent, less durable, and inefficient packaging. This community engagement program aims to improve packaging quality and efficiency through the application of sealer machine technology and capacity building for MSME operators. The implementation methods include socialization, training, mentoring, and structured observation-based evaluation of packaging processes and outcomes. The results indicate clear improvements in packaging quality, particularly in terms of tightness, uniformity, and durability after the use of the sealer machine. Production efficiency also increased, as reflected in faster packaging flow and fewer manual packaging errors. Additionally, the technical skills of MSME operators improved through hands-on training and continued mentoring. Overall, the program demonstrates that the integration of simple sealer technology effectively enhances packaging quality, production efficiency, and strengthens the competitiveness of Seleraku MSME products in the marketplace